ANALISIS DETERMINAN PEMBANGUNAN DESA DI DESA DANGIN PURI KANGIN KOTA DENPASAR - Made Denny Mahatama; Made Kembar Sri Budhi (ADMIN: Jurnal Administrasi Negara, 2023)
Village development is carried out by village officials and assisted by village communities by utilizing the natural resources owned by the village. Villages receive funds from the Central and Regional Governments for the development of their territory, in whose management it is necessary to know the Transparency and Accountability of Village officials in managing Village finances, as well as how Community Participation contributes to Village Development. The purpose of this study is to partially analyze the Effects of Transparency, Accountability, and Community Participation on Village Development in Dangin Puri Kangin Village, Denpasar City and to analyze simultaneously the Effects of Transparency, Accountability, and Community Participation on Village Development in Dangin Puri Kangin Village, Denpasar City. This research is quantitative and associative in nature which will focus on four main variables, namely Transparency, Accountability Community Participation, and Village Development. By using the Slovin formula, the population of this study was 8,182 people by taking 100 samples. Taking the number of research samples in the village of Dangin Puri Kangin was determined using the cluster random sampling method. Data collection was carried out using a questionnaire or questionnaire method by distributing questionnaires in 7 hamlets in Dangin Puri Kangin Village, Denpasar City which will later be used as reference data from this study. This study uses multiple linear regression analysis techniques. Based on the results of the study, it was found that Transparency, Accountability, and Community Participation simultaneously affect Village Development in Dangin Puri Kangin Village, Denpasar City. Transparency, Accountability, and Community Participation variables have a positive and significant effect on Village Development in Dangin Puri Kangin Village, Denpasar City.